Caffeine Therapy for Apnea of Prematurity: Role of the Circadian CLOCK Gene Polymorphism - Guo, Hong-Li; Long, Jia-Yi; Hu, Ya-Hui; Liu, Yun; He, Xin; Li, Ling; Xia, Ying; Ding, Xuan-Sheng; Chen, Feng; Xu, Jing; Cheng, Rui (Frontiers in Pharmacology, 2022)
Standard-dose caffeine citrate has been routinely prescribed for apnea of prematurity (AOP) management; however, some preterm infants respond well to the therapy while others do not. The AOP phenotype has been attributed solely to the immature control of the respiratory system consequent to preterm birth, but there are also important genetic influences. Based on our previous report, we tested the hypothesis that the human circadian locomotor output cycles kaput (CLOCK) gene polymorphisms play a role in the response to caffeine citrate therapy in preterm infants. We also studied the interactions of the circadian clock with aryl hydrocarbon receptor (AHR) signaling pathways in preterm babies who received caffeine citrate. This single-center study collected data from 112 preterm infants (<35 weeks gestational age) between July 2017 and July 2018, including apnea-free (n = 48) and apneic (n = 64) groups. Eighty-eight candidate single nucleotide polymorphisms (SNPs) were tested using the MassARRAY system. Association analysis was performed using the PLINK Whole Genome Data Analysis Toolset and SNPStats software. Linkage disequilibrium (LD) and haplotype analyses were performed using Hapview software. No significant intergroup differences in allele distributions or genotype frequencies of CYP1A2, CYP3A4, CYP3A5, and CYP3A7 were detected in our study on preterm babies. Two more SNPs in AHR were found to be associated with determining the response to caffeine citrate therapy in our pediatric patients. Of the 46 candidate SNPs in the CLOCK gene, 26 were found to be associated with determining the response to caffeine treatment in these babies. Interestingly, a significant association was retained for 18 SNPs in the CLOCK gene after false discovery rate correction. Moreover, strong LD formed in those variants in AHR, ADORA2A, and CLOCK genes was confirmed to be significantly associated with a better response to standard-dose caffeine therapy. In summary, CLOCK gene polymorphisms play a role in determining the response to caffeine therapy in premature neonates with AOP. However, whether the AHR and CLOCK signaling pathways crosstalk with each other during caffeine treatment remains largely unclear. Future clinical studies including more immature babies and basic research are needed to explore the mechanism by which circadian rhythms affect the response to caffeine therapy.